Association of overtime work with cellular immune markers among healthy daytime white-collar employees - Akinori Nakata; Masaya Takahashi; Masahiro Irie (Nordic Association of Occupational Safety and Health (NOROSH), 2012)
OBJECTIVE: Even though overtime work has been suspected to be a risk factor for ill health, little research has been done to determine the underlying immunological mechanisms. This study investigated the association between overtime work and cellular immunity among Japanese white-collar workers. METHODS: A total of 306 healthy, full-time, non-shift, daytime employees (165 men and 141 women), aged 22-69 (mean 36) years, provided a blood sample for the measurement of circulating immune [natural killer (NK), B, and T] cells and NK cell cytotoxicity (NKCC) and completed a questionnaire survey including overtime/month. Blood samples were collected between 09.00-11.00 hours during working days and participants completed the questionnaire within the two weeks prior to the blood sampling. Stepwise linear regression analyses controlling for confounders were carried out to examine the relationship between overtime work and immune markers. RESULTS: Overtime work was mainly related to short sleep duration, increased weight, and reduced job satisfaction, and it was more prevalent among men than women and among younger and married employees. Amount of overtime was inversely associated with NK (CD3-CD56+) cell counts (β=-0.145; P =0.032) but was not associated with NKCC, NKCC/NK cell ratio, or T or B cells. CONCLUSIONS: The NK cell is a lymphocyte that possesses killer activity against tumor and virus-infected cells and constitutes a major component of the innate immune system. A decrease of NK cell counts from overtime work suggests a dampened innate immune defense. However, the finding needs to be further validated with a well-designed study using objective overtime measures.